Polyurethanes as Biomaterials in Medicine: Advanced Applications, Infection Challenges, and Innovative Surface Modification Methods - Drożdż Kamil; Gołda-Cępa Monika; Brzychczy-Włoch Monika (Postępy Mikrobiologii)
Polyurethanes (PUs) are exceptionally versatile polymers widely utilized in medicine due to their outstanding mechanical properties, biocompatibility, and adaptability to various applications. This article explores advanced applications of polyurethane biomaterials in medicine, the challenges posed by infections associated with their use, and innovative surface modification techniques to improve their functionality. PUs are employed in a diverse array of medical devices, including non-implantable applications such as wound dressings, catheters, and infusion sets; short-term implants like bone stabilizers and tracheostomy tubes; and long-term implants such as tissue regeneration scaffolds, artificial blood vessels, and heart valves. Despite their many advantages, their use carries a significant risk of infections, including ventilator-associated pneumonia, infective endocarditis, and urinary tract infections. An important challenge lies in bacterial biofilms, which complicate treatment and enhance bacterial resistance to antibiotics. To address these issues, innovative PU surface modification methods are being developed, including laser texturing, nanoparticle deposition with antibacterial properties, ion implantation, cold metal spraying, the integration of biodegradable and biocompatible components, and plasma modifications. These advanced techniques aim to enhance polyurethane biomaterials’ antibacterial properties and biocompatibility, thereby reducing infection risks and improving clinical outcomes. This article underscores the importance of ongoing research to effectively combat biomaterial-associated infections and broaden the medical applications of polyurethanes. The development of advanced surface modification methods holds great promise for improving patient quality of life and the efficacy of medical treatments.